Reconstitution of immune cell populations in multiple sclerosis patients after autologous stem cell transplantation. (7th June 2017) - Karnell, F. G.; Lin, D.; Motley, S.; Duhen, T.; Lim, N.; Campbell, D. J.; Turka, L. A.; Maecker, H. T.; Harris, K. M.
Summary: Multiple sclerosis is an inflammatory T cell‐mediated autoimmune disease. In a Phase II clinical trial, high‐dose immunosuppressive therapy combined with autologous CD34 + haematopoietic stem cell transplant resulted in 69·2% of subjects remaining disease‐free without evidence of relapse, loss of neurological function or new magnetic resonance imaging (MRI) lesions to year 5 post‐treatment. A combination of CyTOF mass cytometry and multi‐parameter flow cytometry was used to explore the reconstitution kinetics of immune cell subsets in the periphery post‐haematopoietic cell transplant (HSCT) and the impact of treatment on the phenotype of circulating T cells in this study population. Repopulation of immune cell subsets progressed similarly for all patients studied 2 years post‐therapy, regardless of clinical outcome. At month 2, monocytes and natural killer (NK) cells were proportionally more abundant, while CD4 T cells and B cells were reduced, relative to baseline. In contrast to the changes observed at earlier time‐points in the T cell compartment, B cells were proportionally more abundant and expansion in the proportion of naive B cells was observed 1 and 2 years post‐therapy. Within the T cell compartment, the proportion of effector memory and late effector subsets of CD4 and CD8 T cells was increased, together with transient increases in proportions of CD45RA‐regulatory T cells (Tregs ) and T helper type 1 (Th1 cells) and a decrease in Th17·1 cells. While none of the treatment effects studied correlated with clinical outcome, patients who remained healthy throughout the 5‐year study had significantly higher absolute numbers of memory CD4 and CD8 T cells in the periphery prior to stem cell transplantation. Abstract : A combination of CyTOF mass cytometry and multi‐parameter flow cytometry was used to explore the reconstitution kinetics of immune cell subsets in the periphery post HSCT and the impact of treatment on the phenotype of circulating T cells in the HALT‐MS study population. Within the T cell compartment, the proportion of effector memory and late effector subsets of CD4 and CD8 T cells was increased, together with transient increases in proportions of CD45RA‐ Tregs, and Th1 cells, and a decrease in Th17.1 cells. While none of the treatment effects studied correlated with clinical outcome, patients that remained healthy throughout the 5 year study had significantly higher absolute numbers of memory CD4 and CD8 T cells in the periphery prior to stem cell transplantation.